Form, Function and Meaning of Prefixes Pa- and Particle –Si in Lio Ende - Kami, Patrisius; Niron, Yakobus M. Langkelang; Ga’a, Adi Iswani Habiba (eScience Humanity Journal, 2024)
In this writing, discussed about the Form, Function, and Meaning of the prefix pa- and particle -si in BL in Ende Regency. Please note that prefixes in BL are always found in one form of prefix, namely pa- and particle –si in every speech of the Lio community in general. In BL, other affixes were also found besides the prefix pa- and particle –si, but the subject of this study only focused on these two forms of affixes. In BL there are also no infixes, suffixes, and confixes found. Thispaper aims to describe a subcategory of morphemes in B ahasa Lio (BL) Types of morphemes can be distinguished according to their morphological and semantic behavior. According to its morphological behavior, morphemes consist of bases, free morphemes and bound morphemes. In both types of morphemes can be classified the process of formation, including formed or attached directly with the basic form free of nouns, verbs, and adverbs. In this study can focus more on the shape of pa- and -si bound morphemes in BL.